Fluormacraeite, [(H2O)K]Mn2(Fe2Ti)(PO4)4[OF](H2O)10 ⋅ 4H2O, the first type mineral from the Plößberg pegmatite, Upper Palatinate, Bavaria, Germany - Grey, Ian E; Rewitzer, Christian; Hochleitner, Rupert; Kampf, Anthony R; Boer, Stephanie; Mumme, William G; Wilson, Nicholas C; Davidson, Cameron J (European journal of mineralogy (Stuttgart), 2025)
Fluormacraeite, [(H2O)K]Mn2(Fe2Ti)(PO4)4[OF](H2O)10 ⋅ 4H2O, is a new monoclinic member of the paulkerrite group from the Plößberg pegmatite, Upper Palatinate, Bavaria, Germany. It was found in specimens of magnesium-bearing triplite. Associated minerals are spherical blue phosphosiderite, pink-coloured strengite micro-crystals, white fluorapatite globules, light-yellow leucophosphite, black–green rockbridgeite, and reddish-brown cacoxenite. Fluormacraeite occurs as isolated pale-yellow rhombic tablets, flattened on (010) with diameters in the range of 50 to 150 µm and thicknesses on the order of 10 to 30 µm. The crystal forms are {010}, {001}, and {111}. The calculated density for the empirical formula and single-crystal unit-cell volume is 2.39 g cm−3. Optically, fluormacraeite crystals are biaxial (+), with α=1.610(3), β=1.620(3), and γ=1.644(3) (measured in white light). The calculated 2V is 66.5°. The optical orientation is X=b, Y=c, and Z=a. The empirical formula from electron microprobe analyses and structure refinement is A1[K0.14(H2O)0.76]Σ0.90 A2[K0.79(H2O)0.21]Σ1.00 M1(Mn1.752+Mg0.25)Σ2.00 M2+M3(Fe1.843+Al0.13Ti1.024+Mg0.01)Σ3.00 (PO4)4.00 X[O0.94F0.81(OH)0.25]Σ2.00(H2O)10 ⋅ 3.90H2O.Fluormacraeite has monoclinic symmetry with space group P21/c and unit-cell parameters a=10.546(2) Å, b=20.655(1) Å, c=12.405(1) Å, β=90.09(1)°, V=2702.1(6) Å3, and Z=4. The crystal structure was refined using synchrotron single-crystal data to wRobs=0.0559 for 5646 reflections with I>3σ(I). Fluormacraeite is isostructural with the paulkerrite-group minerals pleysteinite, macraeite, rewitzerite, hochleitnerite, fluor-rewitzerite, sperlingite, and paulkerrite, with ordering of K and H2O at different A sites (A1 and A2) using the general formula A1A2M12M22M3(PO4)4X2(H2O)10 ⋅ 4H2O. It is the F analogue of macraeite, with OF replacing O(OH) at the X2 sites. The general crystal–chemical properties of the monoclinic paulkerrite-group minerals are compared.